التأمين الإجتماعي لغير الأجراء - أحلام بركان; رحمة قيد (My University, 2017)
Summary: Our study allowed for a comprehensive look at developments in the social security system in general. s Republic of Korea ", which has been a distinct system since its inception throughout history because it is the safety system by which members of society are protected within a single State, This system was found in all the countries of the globe and most of the legislation was trying to develop it and it was compulsory. and attempted to cover all members of society, and all the rights advocated by all constitutions and international organizations In this context, the first appearance of the idea of risk protection was under social insurance in the mid-nineteenth century during Bismarck's reign. "Bismarck Von Otto", thus three types of insurance have emerged that deepen the disease, Work accidents, old age and collected in one general rationing, 1911 to spread across all European countries and include other risks such as unemployment and death Although the social insurance system has many advantages, it has not been known to succeed in providing protection and economic security to individuals, A kind of failure to cover all the dangers of society was the beginning of the emergence of a new and more effective system: "The social security system", which from the very beginning has been characterized by a broad trend and comprehensive coverage of all social risks that stare and surround the human person and simplify its effects on all fields. This system can be said to have emerged In the aftermath of World War Aloli, it was not until after World War II that he became aware of an expansion and spread, due to the famous Beveridge William report, which presided over the lunar tasked with studying Britain's social security system, exploring the system, finding stolen points and finding appropriate solutions to eliminate defects. In 1941, the Commission submitted its report only in 1992, which resonated with great resonance not only in Britain but also in all countries that were developing their social system. .................................... الملخص : لقد سمحت دراستنا بإعطاء نظرة شاممة حول التطورات التي شهدها نظام الضمان الإجتماعي بصفة عامة، هذا الأخير الذي يعد منظومة متميزة منذ نشأتها عبر التاريخ كونها تعد نظام الأمان الذي يحمي به أفراد المجتمع داخل الدولة الواحدة، فوجد هذا النظام في جميع دول المعمورة وكانت معظم التشريعات تحاول أن تطور فيه فجعمته إلزاميا، وحاولت أن تكون تغطيتها تشمل جميع أفراد المجتمع، وجميع الحقوق التي نادت بها جميع الدساتير والمنظمات الدولية، وفي هذا الإطار فإن أول ظهور لفكرة الحماية من الأخطار كان بموجب التامين الإجتماعي في منتصف القرن التاسع عشر أثناء فترة حكم باسمارك "Bismarck Von Otto"، و بالتالي ظهرت ثلاثة أصناف للتأمينات تتعمق بالمرض، وحوادث العمل ، والشيخوخة و تم جمعها في تقنين واحد عام ،1911 لينتشر في جميع الدول الأوروبية ويشمل مخاطر أخرى كالبطالة والوفاة ، وبالرغم من أن نظام التأمينات االجتماعية اتسم بالعديد من المزايا إلا انه لم يعرف نجاحا في توفير الحماية والأمن االقتصادي للأفراد، فقد عرف نوع من الفشل في تغطية كل مخاطر المجتمع فكان ذلك بمثابة بداية لظهور نظام جديد وأكثر فعالية وهو " نظام الضمان االجتماعي " الذي تميز منذ الوهلة الأولى باتجاه واسع و تغطية شاملة لكل المخاطرالإجتماعية التي تحدق وتحيط بالإنسان وتبسط آثاره على جميع الميادين بها وهذا النظام يمكن القول انه ظهر في أعقاب الحرب العالمية األولى ، ثم لم يعرف توسعا وانتشارا إلا بعد أعقاب الحرب العالمية الثانية ويعود ذلك إلى تقرير الشهير بيفريدج "Beveridge William "الذي ترأس المجنة المكلفة بدراسة نظام الضمان الإجتماعي لبريطانيا واستكشاف المنظومة والوقوف على نقاط السلب وإيجاد الحلول المناسبة للقضاء على العيوب، وقد نصبت اللجنة عام 1941 ولم تقدم تقريرها إلا عام ،1992 هذا التقرير الذي كان له صدى كبير ليس في بريطانيا فقط بل كل الدول التي كانت تصبوا إلى تطوير منظومتها االجتماعية. .................................... Résumé : Notre étude a permis de faire un examen complet des développements du système de sécurité sociale en général. République de Corée ", qui a été un système distinct depuis sa création tout au long de l’histoire parce qu’il est le système de sécurité par lequel les membres de la société sont protégés dans un seul État, Ce système a été trouvé dans tous les pays du globe et la plupart des législations essayaient de le développer et il était obligatoire. Dans ce contexte, la première apparition de l’idée de protection des risques a eu lieu sous assurance sociale au milieu du XIXe siècle sous le règne de Bismarck. "Bismarck Von Otto", ainsi trois types d’assurance ont émergé qui approfondissent la maladie, les accidents du travail, la vieillesse et réunis en un rationnement général, Le système d’assurance sociale présente de nombreux avantages, mais il n’a pas réussi à assurer la protection et la sécurité économique des individus, Une sorte d’échec à couvrir tous les dangers de la société a été le début de l’émergence d’un système nouveau et plus efficace : "Le système de sécurité sociale", qui a été depuis le début caractérisé par une tendance large et une couverture complète de tous les risques sociaux qui fixent et entourent la personne humaine et simplifient ses effets dans tous les domaines. Ce système peut être considéré comme étant apparu Après la guerre mondiale, Aloli n’a pas pris conscience de l’expansion et de la propagation de la maladie avant la fin de la seconde guerre mondiale, à cause du fameux rapport Beveridge William, qui présidait le comité lunaire chargé d’étudier le système de sécurité sociale britannique, d’explorer le système, Trouver les points volés et trouver des solutions appropriées pour éliminer les défauts. En 1941, la Commission ne présenta son rapport qu’en 1992, qui eut un retentissement non seulement en Grande-Bretagne mais aussi dans tous les pays qui développaient leur système social.